An empirical analysis between Bank Islam Malaysia Berhad (Islamic banking) and Public Bank (Conventional banking) / Aina Syakira Jamaluddin - Jamaluddin, Aina Syakira (Faculty of Business and Management, 2013)
Malaysia banking sector has the largest assets of both Islamic and conventional banking. Conventional and Islamic banks are operating side by side in the market. However, the rapid growth of Islamic banking system in Malaysia creates intensive competitions in the industry. Each bank tries to be more financially feasible than others by increasing activities and innovating some products to gain higher market share. Therefore, there is an urgent need to make comprehensive analysis of Malaysia banks performance, since there have been limited studies on the financial performance of Islamic bank and conventional banks in the country. The aim of this paper is to evaluate and analyses the impact of bank specific as well as macroeconomic determinant on the profitability of Malaysia Islamic banking which represented by Bank Islam Malaysia Berhad (BIMB) compare with conventional banking which is Public Bank Berhad. The research applied the performance evaluation of both banking segment that covers 5 year period range from 2007-2011. However, this paper used the performance evaluation methodology by conducting the probability, liquidity and leverage ratio tests. For completion of this report, secondary data and other approaches has been used as data collection. This data are taken from internal sources such as Annual Financial Report of both banks and external sources such as journal, books and internet. The result imply that